(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to describe clinical and paraclinical of patients with septicemia caused by ESBL-producing E.coli at Bach Mai Hospital in the period 2021-2022. Subject and methods: Cross-sectional descriptive study conducted on 87 patients treated at Bach Mai Hospital in the period 2021-2022 with a diagnosis of septicemia caused by ESBL-producing E. coli. Results: Among 87 patients treated for sepsis caused by ESBL-producing E.coli, the rate of community-acquired infection accounted for 75.1%. The most prominent clinical symptoms were fever (80/87), physical examination showed rapid pulse (65.5%) and pulmonary rales in 39.1%. The rate of increase in CRP and PCT was >66%. Common lesions are abdominal fluid and dilatation and hydronephrosis on ultrasound. – ureters (18.4%), gallstones, urinary stones (16.1%), hepatosplenomegaly (13.8%). The study’s Pitt bacteremia score was 1.35 ± 1.48; community group (1.38) and hospital group (1.24). Conclusions: The majority of cases are caused by bacteremia in the community. The respiratory and cardiovascular systems exhibit the most frequent physical symptoms. There were 71.3 and 66.7% more patients with elevated CRP and PCT, respectively. Common lesions on ultrasound include abdominal fluid and dilation, hydronephrosis - ureter, gallstones, urinary stones, and hepatosplenomegaly.There was no difference in severity and mortality prognosis between community and hospital infection groups.